Photoinduced phenomena in thin-film Cu-PbI₂ and Cu-PbI₂-chalkogenide glassy semiconductor systems - Mussil, V.V.; Lemeshevskaya, E.T.; Pilipenko, V.V. (Functional Materials, 2006)
Results of photoinduced processes study in two-layer Сu-РbI₂ and three-layer Сu-РbI₂- chalkogenide glassy semiconductor (Ge-As-S) systems are presented. Reversible changes of optical transmittance in Сu-РbI₂-Ge-As-S systems under consecutive irradiation with different wavelength light (442 and 633 nm) have been found. It has been established that irradiation of the systems with linearly polarized weakly absorbed light results in formation of periodic diffraction structures. The phenomena observed have been considered taking into account the Сu photodiffusion processes, formation and degradation of small metallic particles in the РbI₂ layer and the light waveguide propagation in the film systems. Представлены результаты исследования фотоиндуцированных процессов в двух- и трехслойных системах Сu-РbI₂ и Сu-РbI₂-халькогенидный стеклообразный полупроводник (Ge-As-S). Обнаружены обратимые изменения оптического пропускания систем Сu-РbI₂-Ge-As-S при последовательном воздействии на них излучения с различными длинами волн (442 и 633 нм). Установлено, что облучение систем слабопоглощаемым линейно поляризованным излучением приводит к формированию в них периодических дифракционных структур. Наблюдаемые явления проанализированы с учетом процессов фотодиффузии Сu, образования и разрушения мелких металлических частиц в слое РbI₂ и волноводного распространения света в пленочной системе. Наведено результати дослiдження фотоiндукованих процесiв у двох- i трьохшарових системах Сu-РbI₂ та Сu-РbI₂-халькогенiдний склоподiбний напiвпровiдник (Ge-As-S). Виявлено оборотнi змiни оптичного пропускання систем Сu-РbI₂-Ge-As-S при їх послiдовному опромiненнi свiтлом з рiзними довжинами хвиль (442 i 633 нм). 3найдено, що опромiнення систем лiнiйно поляризованим свiтлом, що слабо поглинається, призводить до утворення в них дифракцiйних перiодичних структур. Явища, що спостерiгаються, проаналiзовано з урахуванням процесiв фотодифузiї Сu, утворення i руйнування дрiбних металевих частинок у шарi РbI₂ та хвилеводного розповсюдження свiтла у плiвковiй системi.